Application of the curvature smoothing technique for four-node quadrilateral Reissner-Mindlin plate element - Hung, Nguyen Xuan; Phong, Ngo Thanh (Vietnam Journal of Mechanics, 2007)
A quadrilateral element with smoothed curvatures for Reissner-Mindlin structure plates is proposed. A curvature matrix at an arbitrary point is normalized by a non-local approximation over a smoothing function. By choosing a constant smoothed function and applying the divergence theorem, the bending stiffness matrix calculated on boundaries of smoothing elements (smoothing cells) instead of on their interior. Several numerical results are analyzed to demonstrate high reliability and free locking of the proposed method.